Structural vulnerability and transformation: Their links and the LDC5 Monitor consistency - Patrick Guillaumont (Fondation pour les études et recherches sur le développement international (FERDI), 2024)
The purpose of the LDC5 Monitor is twofold: firstly, to assess the vulnerability of LDCs and the means used to deal with it, and secondly, to examine the structural transformation of LDCs in line with the Doha Development Agenda (DDA). Vulnerability and structural transformation, neither of these terms, although used since the early days of development economics, is used in a perfectly clear and unambiguous way, while their importance is largely recognised. And the link between the two needs to be clarified.
Keywords: 330; LDC Monitor; Vulnerabilities